Expert consultation on tropical fruit species of Asia: Proceedings of Expert Consulation on Tropical Fruit Species of Asia held at Mardi, Kuala Lumpur, Malaysia, 17-19 May, 1994 - Arora, R.K.; Ramanatha Rao, V.; International Plant Genetic Resources Institute (1996)
These proceedings on the 'Expert Consultation on Tropical Fruit Species of Asia', are an outcome of the meeting held at Serdang, Malaysia from 17-19 May 1994. The meeting was attended by 14 participants which included regional experts representing South, Southeast and East Asia, ICUC, IPGRI-APO Professional Staff and Senior Staff of the Fruit Research Division of MARDI. The publication deals with overall deliberations of the meeting conducted in five technical sessions, the presentations made and the recommendations finalized. It primarily highlights the status reports of the regional experts on tropical fruit species genetic resources and their assessment in the regions of South Asia, Southeast Asia and East Asia. A well synthesized information on germplasm collection, evaluation, documentation, conservation and utilization of tropical fruit species in regional context has been presented giving due weightage to future needs. The major outcome of the meeting was the identification of priority gene pools and the experts unanimously agreed to the following : major fruits-mango, citrus and rambutan; minor fruits-jackfruit, durian and litchi. Additionally, it was agreed to give attention to mangosteen, longan and carambola. Other recommendations dealt with needs for specific collecting to enrich diversity in the identified gene pools as per requirements of national programmes, and the collecting strategies to be adopted. Major emphasis was on research needs for comprehensive evaluation, pollen storage, in vitro conservation, cryopreservation with emphasis on recalcitrant seeds and stress on complementary conservation strategies including in situ conservation. Much concern was also expressed to collect information on local knowledge, ecogeographic surveys and assessment of genetic diversity. Emphasis was laid on documentation of data, exchange of PGR information and material for mutual benefit. Further, training needs were identified with major emphasis on maintenance, conservation and management aspects of tropical fruit species, establishment of field gene banks etc., apart from collecting, evaluation and documentation needs. The group also identified some centres/institutes with necessary information and expertise, to conduct such short regional training courses.